Crash characteristics of on-road single-bicycle crashes: an under-recognised problem. Issue 5 (14th February 2019) - Beck, Ben; Stevenson, Mark R; Cameron, Peter; Oxley, Jennie; Newstead, Stuart; Olivier, Jake; Boufous, Soufiane; Gabbe, Belinda J
Abstract : Compared with crashes with motor vehicles, single-bicycle crashes are an under-recognised contributor to cycling injury and the aetiology is poorly understood. Using an in-depth crash investigation technique, this study describes the crash characteristics and patient outcomes of a sample of cyclists admitted to hospital following on-road bicycle crashes. Enrolled cyclists completed a structured interview, and injury details and patient outcomes were extracted from trauma registries. Single-bicycle crashes (n=62) accounted for 48% of on-road crashes and commonly involved experienced cyclists. Common single-bicycle crash types included loss-of-control events, interactions with tram tracks, striking potholes or objects or resulting from mechanical issues with the bicycle. To address single-bicycle crashes, targeted countermeasures are required for each of these specific crash types.